Ectopic third molar as a cause of sinusitis - Monti, Lira Marcela [UNESP]; Souza, Josue Gomes de [UNESP]; Pires Soubhia, Ana Maria [UNESP]; Gaetti-Jardim Júnior, Elerson [UNESP] (My University, 2014)
Ectopic third molar teeth are those that are impacted in unusual positions, or that have been displaced and are at a distance from their normal anatomic location. Ectopic eruption of a tooth within the oral cavity is common, but rare in other sites. Ectopic eruption can be associated with developmental disturbances, pathologic processes or iatrogenic activity. Male, 19- years old, with an upper left ectopic third molar located in the maxillary sinus-infraorbital region. The patient reported a bad taste and recurrent sinusitis that had been resistant to treatment. Surgical excision was carried out of the third molar tooth using the Caldwell-Luc approach.

Los cordales ectópicos son aquellos incluidos en posiciones inusuales o desplazados a distancia de su normal localización anatómica. La erupción ectópica de un diente dentro de la cavidad oral es común pero en otros lugares es raro. La erupción ectópica puede ir asociada con alteraciones en el desarrollo, procesos patológicos o yatrogenia. Hombre,19 años de edad con tercer molar superior izquierdo ectópico a nivel de región infraorbitaria-seno maxilar. Presentaba um mal sabor y sinusitis recurrente resistente a tratamiento médico. Se realizó exéresis quirúrgica de dicho cordal mediante abordaje de Caldwell-Luc.

Terceiros Molares ectópicos são aqueles que se encontram em locais incomuns ou deslocados de sua localização anatômica normal. A erupção ectópica de dentes dentro da cavidade oral é comum, mas em outros locais é algo raro. Os dentes ectópicos podem estar associados com, alterações no desenvolvimento, processos patológicos e iatrogenias. Homem, 19 anos de idade com terceiro molar superior esquerdo ectópico em região infraorbitária de seio maxila, relatou gosto ruim e quadro de sinusite recorrente resistente à tratamento médico. Foi realizada cirurgia, para retirada do dente, através da técnica de Cardwell-Luc.
Ectópico tercer molar como una causa de la sinusitis
Terceiro molar ectópico como causa de sinusite
Keywords: Sinusitis; Third molar; Pathology, Infraorbital region; Sinusitis; Tercer molar; Patología; Región infraorbitario; Sinusite; Terceiro molar; Patologia; Região infra orbitária